Financial management practices of micro, small and medium Enterprises in the Obuasi Municipality. - Nketsia, Rufus Eshun (KNUST, 2025)
A Thesis submitted to the Department of Accounting and Finance in partial fulfilment of the requirements for the degree of master of business administration(finance option).